The Determinants of Corporate Tax Aggressiveness in Indonesia - Bani Alkausar; Imam Subekti; Endang Mardiati (e-2477-1929)
This study aims to examine the effect of corporate governance on corporate tax aggressiveness in Indonesia during the year 2013-2015. This study adds related parties’ transactions as a moderator variable to answer the results of previous studies that are not consistent. The population in this study uses manufacturing companies that are listed on the Indonesia Stock Exchange. The selection of manufacturing companies as subjects is based on the tendency that manufacturing firms are more aggressive with taxes. Research data obtained from the annual report which is on the official site idx.co.id, then analyzed using the hierarchy analysis technique or hierarchy regression technique. The results show that corporate governance can reduce the tendency of corporate tax aggressiveness. In addition, related parties’ transactions are proven to lead to the implementation of corporate governance to prevent tax aggressiveness from becoming ineffective.